FRI0261 Anti-phospholipid antibodies in systemic sclerosis: Prevalence and clinical correlations. (23rd January 2014) - Morrisroe, K.B.; Stevens, W.M.; Byron, J.; Thakkar, V.; Moore, O.; Proudman, S.; Nikpour, M.
Abstract : Background: Anti-phospholipid antibodies (APLA) are typically associated with thrombosis in systemic lupus erythematosus and anti-phospholipid syndrome. However, little is know about the clinical associations of these antibodies in systemic sclerosis (SSc). Objectives: We sought to determine the prevalence and correlates of APLA in a large cohort of patients with SSc. Methods: Patients participating in the Australian Scleroderma Cohort Study who fulfilled the ACR or Medsger criteria for SSc, were tested for APLA (anti-cardiolipin IgM [ACA IgM], anti-cardiolipin IgG [ACA IgG] and anti-beta2 glycoprotein antibodies [Anti-β2 GP]) using commercial ELISA assays at each annual visit. APLA and various clinical manifestations were defined as present ever from SSc diagnosis. Chi-square and unadjusted logistic regression were used to identify and quantify clinical associations of APLA in SSc. Results: One or more types of APLA were present in 226 (24.0%) of 940 patients included in the study. There were no patients with lupus anticoagulant. Type and titre of APLA are summarized in Table 1 . Moderate to high titre ACA IgG were associated with right heart catheter-diagnosed pulmonary arterial hypertension (PAH) (odds ratio 1.6, 95% CI: 1.03-2.52, p=0.038). Both ACA IgM (odds ratio 2.04, 95% CI: 1.4-3.0, p<0.0001) and ACA IgG (odds ratio 1.84, 95% CI: 1.2-2.8, p=0.005) were associated with interstitial lung disease (ILD). ACA IgG was a marker of coexistent PAH and ILD (odds ratio 2.10, 95% CI: 1.1-4.2, p=0.036). There was no association between APLA and SSc disease subtype (limited v. diffuse), presence of other autoantibodies, or other disease manifestations e.g. renal crisis. Conclusions: Anti-phospholipid antibodies are found in 24% of patients with SSc, but in most cases the titres are low (<20 U/ml). Moderate to high titre APLA are associated with a 1.6 to 2-fold increased risk of PAH or ILD, and a 2-fold increased risk of coexistent PAH and ILD in SSc. Disclosure of Interest: None Declared